Harga Dan Kualitas Produk Terhadap Keputusan Pembelian dengan Promosi Sebagai Variabel Moderasi pada E-Commerce Zalora - Yola Yolanda; Naca Perangin-Angin; Purnaya Sari Tarigan; Anita Tarihoran (Universitas Methodist Indonesia, 2024)
The purpose of this research is to determine and analyze the influence of price and product quality on purchasing decisions with promotional capabilities in moderating at Zalora e-commerce among Mikroskil University students. The sample used non-probability sampling with a purposive sampling approach. Data collection methods were carried out using interviews, questionnaires, documentation and literature study. The data analysis method uses multiple linear regression analysis and regression analysis on moderating variables using the moderated regression analysis (MRA) test method using IBM SPSS version 25 software. The research results simultaneously show that price and product quality variables have a significant effect on purchasing decisions. Partially, the price and product quality variables have a significant effect on purchasing decisions. The results of testing the moderating variable show that the promotion variable is unable to moderate the relationship between price and product quality variables with purchasing decisions.